2015
DOI: 10.1038/cddis.2015.198
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between muscle stem cells, mesenchymal-derived cells and immune cells in muscle homeostasis, regeneration and disease

Abstract: Recent evidence has revealed the importance of reciprocal functional interactions between different types of mononuclear cells in coordinating the repair of injured muscles. In particular, signals released from the inflammatory infiltrate and from mesenchymal interstitial cells (also known as fibro-adipogenic progenitors (FAPs)) appear to instruct muscle stem cells (satellite cells) to break quiescence, proliferate and differentiate. Interestingly, conditions that compromise the functional integrity of this ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
106
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(108 citation statements)
references
References 181 publications
1
106
0
1
Order By: Relevance
“…Muscle regeneration, senescence, inflammation, oxidative stress, and apoptosis are all cellular processes that influence muscle mass and therefore may play a role in the development or protection from sarcopenia during ageing . Accumulating evidence suggests that these complex cellular processes, alongside increased cytokine activity, play a role in satellite cell activation and differentiation during muscle fibre repair and remodelling in humans . There have been prior studies comparing skeletal muscle in healthy elderly adults with those with pathologies including cancer, but studies in healthy elderly adults without sarcopenia, which assess multiple biomarkers of muscle regeneration and underlying cellular processes in tandem in the same human muscle biopsies are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Muscle regeneration, senescence, inflammation, oxidative stress, and apoptosis are all cellular processes that influence muscle mass and therefore may play a role in the development or protection from sarcopenia during ageing . Accumulating evidence suggests that these complex cellular processes, alongside increased cytokine activity, play a role in satellite cell activation and differentiation during muscle fibre repair and remodelling in humans . There have been prior studies comparing skeletal muscle in healthy elderly adults with those with pathologies including cancer, but studies in healthy elderly adults without sarcopenia, which assess multiple biomarkers of muscle regeneration and underlying cellular processes in tandem in the same human muscle biopsies are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…FAP along with the satellite cells participate in muscle regeneration providing a source of cytokines that regulate satellite cell activity and establishing an environment enhancing myogenic differentiation. 4 However, under pathological conditions, FAPs may impair muscle structure and function. Uezumi et al 5 demonstrated a participation of FAPs in the ectopic fat formation in skeletal muscle and the replacement of the skeletal muscle with fibrofatty tissue in the mouse model of Duchenne muscular dystrophy, which exhibits some histological similarities with ARVD/C.…”
Section: Article See P 41mentioning
confidence: 99%
“…fibro-adipogenic progenitors -FAPs) and MuSCs appear a key determinant to drive the skeletal muscle toward a regeneration or degeneration process. [6,7] This notion has inspired a number of current pharmacological strategies aimed at targeting these cells and the functional networks they establish, [8,9] as an alternative to gene replacement and cell-based strategies.…”
Section: Hdac Inhibitors For Muscular Dystrophies: Progress and Prospmentioning
confidence: 99%